PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Telekomunikasi yang Terdaftar di BEI) - Prabawa, Santosa Tri (JURNAL ILMIAH EDUNOMIKA, 2024)
The phenomenon that occurred during the Covid 19 pandemic was that many telecommunications companies that went public developed well, even though during the pandemic many companies experienced large losses and even went bankrupt. The problem in this research aims to determine the effect of profitability and liquidity on company value with company size as a moderating variable in telecommunications companies listed on the IDX for the 2019 - 2021 period. The type of research used is quantitative research with secondary data sources. The population in this study were 19 telecommunications service companies listed on the Indonesia Stock Exchange for the 2019 - 2021 period. The sample was taken using a purposive sampling technique of 16 companies that met the criteria. The data analysis technique uses multiple linear regression analysis techniques and regression analysis with moderating variables. The research results show that profitability and liquidity are able to influence company value, while capital structure is not able to influence company value. The company size variable is unable to moderate profitability, capital structure and liquidity on company value.